A systematic review and meta-analysis of cognitive processing deficits associated with body dysmorphic disorder. (August 2018) - Johnson, Shevaugn; Williamson, Paul; Wade, Tracey D.
Abstract: This systematic review and meta-analysis examined the evidence supporting the association between body dysmorphic disorder (BDD) symptomology and four types of cognitive processing abnormalities: local processing, selective attention, interpretive biases, and memory deficits. Twenty-three studies met inclusion requirements that examined differences in performance on cognitive tasks between BDD and control groups across the four categories. Multilevel modelling was used to calculate an overall effect size for each cognitive category. BDD and control groups differed significantly on measures of selective attention ( g  = 0.60, 95% CI = 0.26: 0.93), interpretive biases ( g  = 0.30, 95% CI = . 07: 0.54), and memory deficits ( g =.56, 95% CI = 0.26: 0.87). Differences between the BDD and control groups on measures of local processing did not reach significance. These findings support the hypothesis that people with BDD may selectively attend to perceived threats or to disorder-related stimuli, misinterpret ambiguous stimuli as threatening, overvalue the importance of attractiveness, and have inaccurate coding and recall for facial or bodily stimuli. Recommendations for future research of these specific cognitive deficits in BDD include introducing the use of Modified Dot Probe Paradigms and new treatment targets that can be used as adjuncts to current treatment modalities. Highlights: Cognitive processing abnormalities in Body Dysmorphic Disorder (BDD) were examined. BDD groups were compared to controls. Medium effect sizes for selective attention and memory deficits were found. A small effect size for interpretive biases was found. Use of Dot Probe Tasks to measure selective attention in BDD is proposed.